IMPLEMENTASI METODE SIX SIGMA DAN KAIZEN UNTUK MENINGKATKAN KUALITAS PRODUKSI BAN RADIAL DI PT. XYZ - Rizky Cristopel Sarumpaet; Daniel Andika Napitupulu; Uni Pratama Pebrina Br. Tarigan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The quality of the radial tire production process is a crucial factor in maintaining the competitiveness of the manufacturing industry. However, defects are still found in the radial tire production process at PT. XYZ, which affect efficiency and product quality. This study aims to analyze and propose improvements to the quality of the radial tire production process using the Six Sigma method combined with the Kaizen approach. The research method used is a quantitative approach with the stages of Define, Measure, Analyze, Improve, and Control (DMAIC). The research data were obtained from production and defect data during the observation period. The results show that out of a total production of 98,048 units, there were 3,172 defective units, equivalent to 3.23%. Failure Mode and Effect Analysis (FMEA) indicates that the crease sidewall defect has the highest risk level with an RPN value of 392. Improvement proposals are formulated based on Kaizen principles, while the Control stage focuses on designing process control using P control charts and DPMO indicators. This study is expected to serve as a reference for continuous improvement in production process quality.